A brief survey of new generation networks - Castillo Medina, Carlos Arturo; Salcedo Parra, Octavio José; Forero Rodríguez, Felipe (Visión electrónica, 2014)
This article gathers relevant information that sheds light into the basic principles that motivated the study of the so called Next Generation Networks (NGN). The concepts presented herein include the most recent studies and standards that have been proposed for a suitable operation of NGN. The issues associated to the use of new types of networks and services are illustrated and analyzed; in particular the article illustrates important aspects issues like network architecture, network management and mobility. Additionally, trends for future studies are suggested according to the main challenges of NGN. The current trend suggests that certain key aspects are yet to be solved before establish the actual owner of an NGN network.